#### Answer

(a) $e^{3y}=5$
(b) $e^{-1}=t+1$

#### Work Step by Step

RECALL:
$\ln{x}=y \longrightarrow e^y=x$
Use the rule above to obtain:
(a) $e^{3y}=5$
(b) $e^{-1}=t+1$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) $e^{3y}=5$
(b) $e^{-1}=t+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.